The sweating process promotes toxigenic fungi expansion and increases the risk of combined contamination of mycotoxins in Radix Dipsaci - Ge, Yangyan; Wang, Lulu; Su, Dapeng; Yuan, Qingsong; Xiao, Chenghong; Hu, Min; Kang, Chuanzhi; Guo, Lanping; Zhou, Tao; Zhang, Jinqiang (Frontiers in Microbiology, 2024)
Abstract Sweating is one of the most important processing methods of Chinese medicinal herbs. However, the high temperature and humidity environment required for sweating Chinese medicinal herbs makes it very easy for fungi to breed, especially toxigenic fungi. The mycotoxins produced by these fungi will then contaminate the Chinese medicinal herbs. In this study, we explored the changes in mycobiota, toxigenic fungi, and mycotoxins with and without sweating in Radix Dipsaci (RD), a typical representative of traditional Chinese medicine that requires processing through sweating. We also isolated and identified the toxigenic fungi from RD, whether they were subjected to sweating treatment or not, and examined their toxigenic genes and ability. The results showed that the detection rate of mycotoxins (aflatoxins, ochratoxins, zearalenone, and T-2 toxin) in RD with sweating was 36%, which was 2.25-fold higher than that in RD without sweating. We also detected T-2 toxin in the RD with sweating, whereas it was not found in the RD without sweating. The sweating process altered the fungal composition and increased the abundance of Fusarium and Aspergillus in RD. Aspergillus and Fusarium were the most frequently contaminating fungi in the RD. Morphological and molecular identification confirmed the presence of key toxigenic fungal strains in RD samples, including A. flavus, A. westerdijkiae, F. oxysporum and F. graminearum. These four fungi respectively carried AflR, PKS, Tri7, and PKS14, which were key genes for the biosynthesis of aflatoxins, ochratoxins, zearalenone, and T-2 toxin. The toxigenic ability of these four fungal strains was verified in different matrices. We also found that A. flavus, A. westerdijkiae, and F. oxysporum were isolated in RD both with sweating and without sweating, but their isolation frequency was significantly higher in the RD with sweating than in the RD without sweating. F. graminearum was not isolated from RD without sweating, but it was isolated from RD with sweating. These findings suggest that the sweating process promotes the expansion of toxigenic fungi and increases the risk of combined mycotoxin contamination in RD.